2017
DOI: 10.1080/09658211.2017.1282517
|View full text |Cite
|
Sign up to set email alerts
|

Source memory that encoding was self-referential: the influence of stimulus characteristics

Abstract: Decades of research suggest that encoding information with respect to the self improves memory (self-reference effect, SRE) for items (item SRE). The current study focused on how processing information in reference to the self affects source memory for whether an item was self-referentially processed (a source SRE). Participants self-referentially or non-self-referentially encoded words (Experiment 1) or pictures (Experiment 2) that varied in valence (positive, negative, neutral). Relative to non-self-referent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
31
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 45 publications
8
31
2
Order By: Relevance
“…This is consistent with prior research (e.g., Durbin et al, 2017;Leshikar et al, 2015) and with arguments that self-referenced, negative information is remembered worse because it is less easily connected to the self and therefore effects are primarily evident in source memory (see Durbin et al, 2017).…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…This is consistent with prior research (e.g., Durbin et al, 2017;Leshikar et al, 2015) and with arguments that self-referenced, negative information is remembered worse because it is less easily connected to the self and therefore effects are primarily evident in source memory (see Durbin et al, 2017).…”
Section: Discussionsupporting
confidence: 80%
“…For example, when participants had decided during encoding whether or not a positive adjective was self-descriptive (responding yes or no), they were subsequently more likely to respond "self" rather than "common" or "don't know" when asked which judgment they had been asked to make for that adjective. Replicating this result, Durbin, Mitchell, and Johnson (2017) also found that source memory was better for positive self-referenced words compared to semantic judgment words.…”
Section: The Self-reference Paradigmsupporting
confidence: 57%
See 2 more Smart Citations
“…Other evidence suggests that self-referential processing may improve source memory (i.e., source self-referential effect, e.g., Durbin, Mitchell, & Johnson, 2017) in young adults.…”
Section: The Self and Source Memorymentioning
confidence: 99%